RESEARCH MADE IN INSTITUTE OF COMPUTER SCIENCE - Kozieł, Grzegorz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
In the article the research made in the Institute of Computer Science is presented. The most important areas are presented. Obtained results are described.